KONTRIBUSI KELINCAHAN DAN KECEPATAN TERHADAP KEMAMPUAN DRIBBLE DI EKSTRAKURIKULER FUTSAL SMA N 20 BATAM - Bagus Panrita; M Fransazeli Makarohim (EDU RESEARCH, 2024)
The purpose of this research is to look at how fastness and agility affect futsal dribbling abilities in team sports at SMA Negeri 20 Batam. The study's population included 30 students who were heavily involved in futsal extracurricular activities, and the researchers used a multiple correlation approach to analyze their data. The study's 24 participants were chosen using a purposive selection technique. This research made use of three different tests: the futsal dribbling test, the 40-meter sprint, and the Illinois Agility Run. The Pearson correlation test and relationship degree recommendations were used for data analysis. The results showed that: (1) Agility has a moderate correlation with futsal dribbling skills (f = 0.000 < 0.05 and a relationship degree of 0.451), (2) Speed has a strong correlation with futsal dribbling skills (f = 0.003 < 0.05 and a relationship degree of 0.721), and (3) The combination of speed and agility has a moderate correlation (f = 0.000 < 0.05 and a relationship degree of 0.497).